.333(x-2)+5/6(x-1)=x-3

Simple and best practice solution for .333(x-2)+5/6(x-1)=x-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for .333(x-2)+5/6(x-1)=x-3 equation:



.333(x-2)+5/6(x-1)=x-3
We move all terms to the left:
.333(x-2)+5/6(x-1)-(x-3)=0
Domain of the equation: 6(x-1)!=0
x∈R
We multiply parentheses
0.333x+5/6(x-1)-(x-3)-0.666=0
We get rid of parentheses
0.333x+5/6(x-1)-x+3-0.666=0
We multiply all the terms by the denominator
(0.333x)*6(x-1)-x*6(x-1)+3*6(x-1)-(0.666)*6(x-1)+5=0
We add all the numbers together, and all the variables
(+0.333x)*6(x-1)-x*6(x-1)+3*6(x-1)-(0.666)*6(x-1)+5=0
Wy multiply elements
-6x^2(x+18x(x-(0.666)*6(x-1)+5+(+0.333x)*6(x-1)=0

See similar equations:

| 1/3(x-2)+5/6(x-1)=x-3 | | 2(c+8)=2(2c+1) | | 9(2m+6)=2-8m | | 5a+12=7a-40 | | -8+4a=-6(8+6a) | | X/y=1.2 | | 3/5x-1/2x=10 | | (x-3)(2x+1)=4x+3x+13 | | (x-3)(2x+1)=2x^+3x+13 | | 50=-2x-4x-4 | | 4n^2-8n-99=-3 | | 5(x+2)-2(x-3)=8 | | 2(x+3)=20-x | | 2(4e+1)-2e=9e-1 | | Y=-5/3x+5 | | -x-8+7x=46 | | 2x-(×+2/7)=9 | | 3.5=147+3a/38+a | | x(17-8)=0x-8 | | 7(2x+1)=-105 | | 4=5(w+4)-7w | | 3.5=1*3+2*9+3*a+4*11+5*8+6*7/3+9+a+11+8+7 | | 7+2(x)=11 | | 7+2=3a-10 | | (3x^2+10x+3)(x-5)=0 | | 3x+13=-4x-1 | | 8/5=s+12/5 | | 5x+13=7x+1 | | 7(c-14)=-56 | | -6+2v=-30 | | (X+3)(3x+1)(x-5)=0 | | 81^5x=27^x+3 |

Equations solver categories